Edukasi Financial Wellbeing Untuk Kesehatan Keluarga: Upaya Mengurangi Beban Finansial Pada Generasi Sandwich - Dinna Nurhasanah Dinna Nurhasanah; Yolanda Safitri Nelaz Yolanda Safitri Nelaz; Neni Afriyani Neni Afriyani; Alfitri Yana Alfitri Yana (TANJAK : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve public understanding regarding financial wellbeing among sandwich generation families. The activity was carried out through educational and participatory approaches including counseling, interactive discussions, family financial management simulations, and evaluation involving 30 community participants at Mesjid Ar-Raudhah. The materials presented included family financial planning, emergency fund preparation, debt management, and household financial priority setting. The results showed an increase in participants’ understanding of the importance of healthy and sustainable family financial management. Participants also demonstrated greater awareness of wise financial behavior and long-term financial planning. This activity contributed to improving financial literacy and strengthening family economic resilience among sandwich generation communities.